2009
DOI: 10.1161/circresaha.108.191361
|View full text |Cite
|
Sign up to set email alerts
|

Complement Regulator CD59 Protects Against Atherosclerosis by Restricting the Formation of Complement Membrane Attack Complex

Abstract: Complement is a central effector system within the immune system and is implicated in a range of inflammatory disorders. CD59 is a key regulator of complement membrane attack complex (MAC) assembly. The atherogenic role of terminal complement has long been suspected, but is still unclear. Here, we demonstrate that among mice deficient in apolipoprotein E (Apoe), the additional loss of murine CD59 (mCd59ab−/−/Apoe−/−) accelerated advanced atherosclerosis featuring occlusive coronary atherosclerosis, vulnerable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
124
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 112 publications
(131 citation statements)
references
References 44 publications
6
124
0
1
Order By: Relevance
“…21,40,41 In this article, we show that DAF also plays a role in the regulation of atherosclerosis in the Ldlr Ϫ/Ϫ model. All mice in the study were female.…”
mentioning
confidence: 62%
“…21,40,41 In this article, we show that DAF also plays a role in the regulation of atherosclerosis in the Ldlr Ϫ/Ϫ model. All mice in the study were female.…”
mentioning
confidence: 62%
“…35,37 Cytotoxicity Assay Hep3B cells were used because this cell line has been demonstrated to highly express human CD59. 38 We followed the same protocol as described previously 38,39 to culture the cells and to perform complement-mediated cytotoxicity assay.…”
Section: Determination Of Mac Deposition In Liver Tissuementioning
confidence: 99%
“…In addition to its anti-MAC role, CD59 has a complement-independent function in regulating activity of NK, B, and T cells, 37,40,41 which may also contribute to hepatic IRI. To define the underlying mechanism by which the deficiency of CD59 accelerates the IRI, we generated mCd59ab Ϫ/Ϫ /mC3 Ϫ/Ϫ mice by crossing mC3 C3-deficient mice (mC3 Ϫ/Ϫ ) with mCd59ab Ϫ/Ϫ mice.…”
Section: Accelerated Iri In Cd59-deficient Mice Is Complement Dependentmentioning
confidence: 99%
“…Protectin has a role in prevention of vascular inflammation as indicated by studies on atherosclerosis-prone ApoE Ϫ/Ϫ mice, in which the protectindeficient mice showed signs of accelerated atherosclerosis. 36 In our previous study, we have seen lipid accumulation in the IA wall in same areas with intensive C5b-9 accumulation. 10 Thus, protectin may play a critical role in the IA wall homeostasis.…”
Section: Discussionmentioning
confidence: 62%